STUDI KOMPARASI DISTRIBUSI PENDAPATAN PETANI BERBASIS SAWAH DAN HORTIKULTURA DI KOTA TOMOHON - Andre Konore; Dr. Ir. H. Esry Laoh, MS; Dr. Ir. Paulus A. Pangemanan, MS. (Universitas Sam Ratulangi, 2017)
ABSTRACT The study aims to compare the distribution of the income of farmers in the paddy and horticulture based in Tomohon. The research was conducted from September to November 2016. The data used are primary data obtained through interviews with the 30 (thirty) paddy rice farmer respondents and 30 respondents for farmers Horticulture and secondary data obtained from the Village Office Taratara 1 (one) and Sub Rurukan , Analysis of the data used descriptively by comparing through Lourens curves and Gini index value. The results showed that the Gini index value comparison and Lourens curve is almost the same and into the category of relatively uneven but horticulture farmers' income higher than the income of paddy.